Podocyte Pathology and Nephropathy - Maciej Wojciech Jankowski (Frontiers Research Topics, 2015)
The understanding of the pathogenesis of diabetic nephropathy (DN) has advanced considerably in the last few years. Much has been learned about the natural history, the relative lack of significance of microalbuminuria in reflecting underlying pathological change, questionable effects of ACEs and ARBs on the progression of nephropathy, the emergence of new biomarkers such as Cystatin and the role of cytokines, inflammatory molecules and adhesion molecules. Podocytes, the cells with limited ability to replenish and to repair, play a pivotal role in glomerular filtration. In recent years these cells have become the focus for research on pathogenesis of DN as well as other nephropathies. A recent review from the NIH has identified new insights into the pathophysiology, the genetics and the role of the podocytes and some of the important new metabolic pathways such as mTOR or autophagy which may be targeting the podocyte. Knowledge is emerging about the role of podocyte as a part of immune system and about the role of growth factors and cytokines in regulation of podocyte functions. Presented in this e-book articles highlight recent advances in our understanding of the pathogenesis of kidney pathology and the role of podocytes in this process.